LITERATURE REVIEW : ANALYSIS OF PHYSICAL CONDITION REQUIREMENTS IN SEATED VOLLEYBALL GAMES - Setiyawan, Andri Asrul; Hidayatullah, Muhammad Furqon (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
ABSTRCT This literature review aims to determine several aspects of the physical condition requirements in sitting volleyball games. The method used is literature observation from three electronic databases including Google Scholar, PubMed, and ScienceDirect. This study is based on an examination of 5 studies published between 2013 and 2023 using the SPIDER or Sample, Phenomenon of Interest, Design, Evaluation, and Research type analysis types. The sample used in the reviewed article is elite seated volleyball athletes in their country. The results of the literature review of the 5 articles used in this literature insight show that aspects of physical condition in the sitting volleyball game are very much needed, especially in the upper body and in the training process you must pay attention to various aspects including gender, identification of injuries and type of classification, namely VS1 ( heavy) and VS2 (light). The conclusion from this literature review is that regularly programmed and organized management of physical condition aspects can improve the ability to play seated volleyball in athletes with disabilities. Keywords: physical condition and sitting volleyball